Expanding into the future: Combining a novel dermal template with distinct variants of autologous cultured skin substitutes in massive burns. Issue 3 (July 2021) - Schiestl, Clemens; Meuli, Martin; Vojvodic, Miliana; Pontiggia, Luca; Neuhaus, Diego; Brotschi, Barbara; Reichmann, Ernst; Böttcher-Haberzeth, Sophie; Neuhaus, Kathrin
Highlights: We report the unique case of a 14-year-old boy surviving a 95% BSA burn. The NovoSorb® BTM dermal template was used on a large scale as effective temporary wound coverage. It provided an ideal neodermis for autografts and autologous cultured skin substitutes. Various autologous cultured skin substitutes yielded very high expansion rates. We achieved rapid and stable skin coverage highlighting the huge potential of combining products. Abstract: Background: The management of patients with massive burns remains a challenge. Early burn wound excision followed by timely coverage are key factors of successful surgical treatment. As donor sites are extremely limited, timely coverage requires intermediate wound coverage and expansion of grafts. Although high expansions rates of 1:6 to 1:9 are feasible, they are commonly known to result in poor graft stability and subpar aesthetic outcome. This report aims to illustrate how the availability of three different large-scale laboratory grown autologous tissues used in combination with NovoSorb® BTM allowed not only complete timely coverage, but also provided for a highly favourable outcome in a patient surviving a 95% total body surface area burn (TBSA). Case presentation: We present the case of a 14-year-old who sustained deep flame burns involving 95% TBSA. Only his feet and an area on his scalp were spared, yielding 630 cm 2 of available donor site surface area. A sterile 40 cm 2 split thickness biopsy was taken from the patient's left foot on the day of injury. The biopsy was divided and used for the simultaneous production of cultured epithelial autografts (CEAs) and cultured dermo-epidermal autografts (CDEAs) in Lausanne, as well as Zurich Skin/denovoSkin (dS), a complex autologous cultured dermo-epidermal skin substitute, in Zurich. Over a course of 5 months, 49 surgical procedures were performed. 60% of the patient's TBSA was covered with NovoSorb® BTM while the remaining area received fresh frozen allografts. For definitive coverage, autologous split thickness skin grafts (30% TBSA), CEAs/CDEAs (53% TBSA), and Zurich Skin/dS (12% TBSA) were applied, translating to expansion ratios of 1:8, of 1:383, and of 1:131, respectively. Graft take was excellent for all coverage types with no relevant infectious complications. Conclusions: Sophisticated treatment strategies and innovative surgical methods led to an overall excellent result in this massively burned teenager. The challenge of timely large-scale wound coverage was mastered by applying allografts and NovoSorb® BTM. This is the first report showing successful expansion rates of up to 1:383 in the sequential use of three variants of autologous cultured skin substitutes. This novel approach is highly promising for the management of patients with massive burns.